Diagnostic issues in a family with late onset type 2 neurofibromatosis. Issue 6 (June 1995) - Evans, D G; Bourn, D; Wallace, A; Ramsden, R T; Mitchell, J D; Strachan, T
Abstract : We report a family with type 2 neurofibromatosis and late onset tumours. Five members of this family have developed hearing loss late in life, two of whom have only been shown to have the diagnosis in their seventies, and three other obligate gene carriers died undiagnosed at 64, 72, and 78 years of age. A missense mutation at the C-terminal end of the NF2 protein has been identified in this family and segregates with disease. The use of highly polymorphic markers for predictive testing is also shown. There appears to be an autosomal dominant form of spinocerebellar degeneration which is segregating separately to NF2 in this family, which created a diagnostic dilemma.